2013 22nd International Conference on Noise and Fluctuations (ICNF) 2013
DOI: 10.1109/icnf.2013.6578965
|View full text |Cite
|
Sign up to set email alerts
|

Triple mode-jumping in a spin torque oscillator

Abstract: Abstract-In a nano-contact Co/Cu/NiFe spin torque oscillator, mode-jumping between up to three frequencies within 22.5-24.0 GHz is electrically observed in the time domain. The measurements reveal toggling between two states with differing oscillation amplitude, of which the low-amplitude state is further divided into two rapidly alternating modes. Analysis of the mode dwell time statistics and the total time spent in each mode is carried out, and it is found that in both aspects the balance between the modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Although the higher-frequency mode voltage amplitude was too weak to be observed in the time-domain for sample B, in Ref. 26, a similar behavior was found in similar operating conditions for a similar device and it was unambiguously observed that the STO was constantly jumping between the involved frequencies. As the magnetic field strength is increased, the higherfrequency mode disappears from the spectrum and at 11.5 kOe (Figure 3(b)) the time-domain waveform of the main mode is once again continuous.…”
supporting
confidence: 59%
“…Although the higher-frequency mode voltage amplitude was too weak to be observed in the time-domain for sample B, in Ref. 26, a similar behavior was found in similar operating conditions for a similar device and it was unambiguously observed that the STO was constantly jumping between the involved frequencies. As the magnetic field strength is increased, the higherfrequency mode disappears from the spectrum and at 11.5 kOe (Figure 3(b)) the time-domain waveform of the main mode is once again continuous.…”
supporting
confidence: 59%
“…The occurrence of multiple simultaneously excitable modes is most evident in nanopillar STNOs [169], where the modes emerge as various edge and center modes on account of its confined geometry. In nanocontact STNOs, with their far-extending magnetic films, mode-hopping within the propagating mode has been experimentally observed only at very high drive currents (close to the breakdown of the oscillation), [170] while simultaneous excitability of the propagating and localized bullet mode can also induce mode-hopping [110], [117]. Moreover, the propagating mode in nanocontact STNOs generally exhibits discontinuous mode transitions as a function of the bias point [63], [171], [172].…”
Section: Phase Noisementioning
confidence: 99%
“…Here, the tones are intrinsically linked by rational numbers. Alternatively, mode hopping between nearly degenerate eigen-solutions have been reported (24)(25)(26) induced by thermal fluctuations (27), spatial inhomogeneity of the internal field in asymmetric ferromagnetic bilayers (28), or by formation of higher-order modes of excited magnetic solitons (29). Also, a high level of thermal fluctuations can result in a seemingly multimode generation that is just an amplification of the incoherent thermal population of higher modes.…”
Section: Introductionmentioning
confidence: 99%